Use of Tears as a Biomarker in Ocular Diseases: Use of Tears as a Biomarker in Ocular Diseases - Rani Himayani; Muhammad Azzibaginda Ganie (Medula, 2021)
Tears contain thousands of molecules including proteins / peptides, lipids, electrolytes, and small molecular metabolites which are secreted from the main and accessory lacrimal glands, meibomian glands, goblet cells, and eye surface epithelial cells. Tears are a source of biomarkers for eye and systemic diseases with certain advantages; in particular, non-invasive sample collection and a unique and increasingly better-defined protein composition. Biomarkers are becoming increasingly important in disease diagnosis and drug development because they have the potential to allow for more standard, objective, and precise measurement of disease and / or treatment response to therapy. The search for biomarkers is actually carried out in different body fluids, although the ideal biomarker can be found in easily accessible biological fluids, because if validated they can be searched for in a healthy population. Tears can be considered the optimal source obtained by non-invasive procedures. In recent years, scientific research has begun to focus on the study of tears for new biomarker research not only for eye diseases. In this review, presenting research on current biomarkers in tears and their relevance for clinical practice, and reports on the main results of clinical proteomics studies in eye diseases. Biomarker research in eye diseases, involving characterization of molecular and cellular components, is important to advance our understanding. about disease and developing therapy. However, this is also challenging because of the limited access to the patient's eye specimen Keywords: Essential Oils, Antibacterial, Antiviral, Antioxidant, Anti-inflammatory